2021
DOI: 10.3390/brainsci11040467
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Transcranial Direct Current Stimulation as a Potential Treatment of Parkinson’s Disease-Related Fatigue

Abstract: In contrast to motor symptoms, non-motor symptoms in Parkinson’s disease (PD) are often poorly recognized and inadequately treated. Fatigue is one of the most common non-motor symptoms in PD and affects a broad range of everyday activities, causes disability, and substantially reduces the quality of life. It occurs at every stage of PD, and once present, it often persists and worsens over time. PD patients attending the 2013 World Parkinson Congress voted fatigue as the leading symptom in need of further resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Repetitive anodal tDCS stimulations over the left DLPFC also positively affected fatigue ratings in people with Parkinsons-related fatigue that lasted up to three months ( 104 ). Another study demonstrated that repetitive anodal tDCS sessions over the left DLPFC in a home-treatment context were well tolerated and positively affected subjective fatigue in people with Parkinsons-related fatigue ( 105 ), also see Zaehle ( 106 ) for a recent review.…”
Section: Non-invasive Brain Stimulation As a Therapeutic Option For F...mentioning
confidence: 99%
“…Repetitive anodal tDCS stimulations over the left DLPFC also positively affected fatigue ratings in people with Parkinsons-related fatigue that lasted up to three months ( 104 ). Another study demonstrated that repetitive anodal tDCS sessions over the left DLPFC in a home-treatment context were well tolerated and positively affected subjective fatigue in people with Parkinsons-related fatigue ( 105 ), also see Zaehle ( 106 ) for a recent review.…”
Section: Non-invasive Brain Stimulation As a Therapeutic Option For F...mentioning
confidence: 99%
“…Several studies have emphasized that motor symptoms, such as those affecting the isometric grip test and hand dexterity, were improved after anodal tDCS of the motor cortex ( 15 , 46 , 47 ). However, non-motor symptoms of PD, such as depression, fatigue, and frontal executive function, were improved after anodal tDCS on the frontal cortices ( 19 ). In addition to the stimulation site, stimulation intensity, duration, and polarity could differentially affect cortical excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, tDCS has been widely studied for its efficacy in various neurodegenerative disorders ( 12 ). Many studies have shown the beneficial effects of tDCS on various symptoms in PD ( 9 , 13 19 ). Ishikuro et al reported that anodal tDCS in the frontal polar area improved the motor and executive function of patients with PD, and some meta-analytic studies have indicated that tDCS could have a positive effect on locomotive and gait function in PD, despite insufficient sample power to draw firm conclusions in most studies ( 15 , 18 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a technique, tDCS has been extensively studied in the context of PD and numerous studies have demonstrated its effectiveness in improving various aspects of the disease, such as gait [34], cognitive deficits [35], fatigue [36], and balance and functional mobility [37]. However, it is important to note that the effectiveness of tDCS specifically for treating depression in PD has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%